A Liquid-Based System for CPU Cooling Implementing a Jet Array Impingement Waterblock and a Tube Array Remote Heat Exchanger - ROBINSON, ANTHONY; KEMPERS, ROGER (My University, 2012)
A liquid CPU cooler has been designed and tested with the aim to achieve a cooling capacity of 200 W for a surface area of 8.24 cm2, commensurate with the integrated heat spreader dimensions of an Intel? Pentium? 4 Processor. The primary aim of the design was to develop thermal hardware components that can be manufactured simply and cost effectively. To this end, a miniature jet array waterblock and a tube bundle remote heat exchanger were employed since the bulk of their housings could be manufactured using low cost injection molding techniques which could significantly reduce the total system cost compared with conventional units. The system was capable of dissipating the required heat load and exhibited an overall thermal resistance of 0.18 K/W requiring approximately 1.5 W of hydraulic power. At maximum power the chip-to-air temperature difference was 45?C which is adequately close to typical design thresholds. The influences of power loading and liquid volumetric flow rate are also discussed.
PUBLISHED
Keywords: Thermal engineering; Electronics Cooling